Model Pembelajaran Window Shopping Meningkatkan Kemampuan Bicara Bahasa Arab Siswa - Lilis, Lilis Elawati; Agustiar; Nandang Sarip Hidayat; Muhammad Azhar; Lidia Fitri (Ukazh: Journal of Arabic Studies, 2025)
Speaking proficiency in Arabic is a fundamental language skill that supports students’ religious comprehension, particularly within the context of Islamic schools (madrasah). However, the limited frequency of speaking practice, low levels of student self-confidence, and the use of less interactive teaching methods present significant barriers to the development of this competency. In response to these challenges, this study aims to evaluate the effectiveness of the windows shopping learning model in enhancing the Arabic speaking skills of eighth-grade students at MTs Pondok Pesantren Nurul Huda, Indragiri Hulu. Employing a quantitative approach with a quasi-experimental design, data were collected through pre- and post-tests and analyzed using a t-test and N-Gain calculation. The findings reveal that the implementation of the windows shopping model has a significant positive effect on improving students' Arabic speaking abilities. This model effectively fosters an active and communicative learning environment through independent exploration, peer dialogue, and oral presentation, all of which encourage direct student engagement. The novelty of this study lies in the application of the windows shopping model within the Arabic language learning context—an area where its use has previously been more common in social studies instruction. This model holds promise as a reference for madrasah curriculum development policies focused on active learning and offers an alternative strategy for enhancing students’ oral communication skills in a contextual, participatory, and meaningful manner.